Pengolahan Limbah Kepala Udang Sebagai Pakan Ikan Patin - Wahyudi, Muhammad; Hidayat, Dedy Rahmat; Amelda, Amelda; Riyadi, Muhammad; Anggraeni, Fitri; Ramadhani, Anindya Salsabila; Aulia, Eva; Sofyannor, Sofyannor; Khasanah, Mitha Sri; Marsiah, Marsiah (Lembaga Dongan Dosen, 2023)
Feed is an important factor in fish farming because it greatly influences the performance of fish which includes growth and reproduction. One alternative material that can be used as a substitute for bran in feed formulations is waste from shrimp processing in the form of shrimp heads. The nutrient content of the shrimp head includes: 31.41% protein, 6.62% fat, 5.59% crude fiber, 3.75Kcal/g energy. Use of shrimp waste heads in feed formulation on protein retention and energy retention in catfish fry. The research was conducted in July – September 2023 in Halimaung Jaya Village located in the father's catfish pond cultivation. The aim of this study was to determine the effect of using shrimp head waste in feed formulas on the growth and development of catfish.